MYASTHENIA GRAVIS, DIAGNOSIS AND TREATMENT - Anom Arie W, A.A Gde Agung; Adnyana, Made Oka; Widyadharma, I Putu Eka (E-Jurnal Medika Udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE Myasthenia gravis is one characteristic of autoimmune disease caused by the disruption of synaptic transmission at the neuromuscular junction. It is characterized by a progressive weakness and abnormal skeletal muscle used continuously and accompanied by fatigue on exertion. knowledge of normal anatomy and function of the neuromuscular junction is very important for understanding about myasthenia gravis,.Presynaptic membrane (membrane nerve), post-synaptic membrane (membrane of the muscle), and the synaptic gap forming part of the neuromuscular junction. Immunogenic mechanism plays a very important in the pathophysiology of myasthenia gravis, in which the antibody is the product of B cells is precisely against the acetylcholine receptor. Management of myasthenia gravis to do with drugs, thymomectomy or with immunomodulating and immunosuppressive therapy that can provide a good prognosis in the healing myasthenia gravis. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Myasthenia gravis, Neuromuscular junction, Management